Posterior Reversible Encephalopathy Syndrome in severe preeclampsia: case report and literature review - Aygun, Banu Kumbak; Baykus, Yakup; Berilgen, Said; Kavak, Burcin; Celik, Husnu; Gurates, Bilgin (Galenos Yayincilik, 2010)
We describe a 23 year old primigravid patient with severe preeclampsia complicated by posterior reversible encephalopathy syndrome (PRES), who presented with sensory and motor deficits and amnesia in the postpartum period Cranial magnetic resonance imaging (MR1) showed abnormal areas in the white matter of bilateral parieto-occipital lobes, indicating brain edema which disappeared completely on the follow-up scan taken four weeks after delivery together with complete symptom regression. The development of PRES in preeclampsia is discussed and the importance of prompt postpartum blood pressure control is emphasized.
A?ır preeklampside posterior reverzibl ensefalopati sendromu: Olgu sunumu ve literatürün gözden geçirilmesi
Keywords: Posterior reversible encephalopathy syndrome (PRES); preeclampsia; pregnancy